Historical and geospatial reconstruction of a sector of the alternative route of the railway to the Atlantic (years 1871-1873), called: "Fajardo line", in a geographical area associated with the valleys of Orosi and Ujarrás, Cartago, Costa Rica - Sanabria Coto, Iván Josué (2022)
This work consists of a historical and geospatial reconstruction, using Geographic Information Systems (GIS), of a sector of the alternative route of the Costa Rican Atlantic railway called: "Fajardo line", built between 1871-1873 and later abandoned. It was promoted by the government of Tomás Guardia Gutiérrez and executed by the North American contractor Henry Meiggs Keith. At the time, this work included, geographically, the north and west of the colonial valleys of Orosi and Ujarrás respectively, in the province of Cartago. This research covered the compilation of documents (historical), and geospatial inputs, as well as the identification, analysis, and integration, through GIS, of construction traces of civil works and evidence of associated anthropic activity, within the study area. As a result, it was possible to geospatially reconstruct the original railway route in the geographic sector of interest, through a reliable, methodological integration of the different identified evidence.